Melatonin Attenuates Sepsis-Induced Small-Intestine Injury by Upregulating SIRT3-Mediated Oxidative-Stress Inhibition, Mitochondrial Protection, and Autophagy Induction - Xu, Siqi; Li, Lulan; Wu, Jie; An, Sheng; Fang, Haihong; Han, Yunyang; Huang, Qiaobing; Chen, Zhongqing; Zeng, Zhenhua (Frontiers in Immunology, 2021)
Melatonin reportedly alleviates sepsis-induced multi-organ injury by inducing autophagy and activating class III deacetylase Sirtuin family members (SIRT1–7). However, whether melatonin attenuates small-intestine injury along with the precise underlying mechanism remain to be elucidated. To investigate this, we employed cecal ligation and puncture (CLP)- or endotoxemia-induced sepsis mouse models and confirmed that melatonin treatment significantly prolonged the survival time of mice and ameliorated multiple-organ injury (lung/liver/kidney/small intestine) following sepsis. Melatonin partially protected the intestinal barrier function and restored SIRT1 and SIRT3 activity/protein expression in the small intestine. Mechanistically, melatonin treatment enhanced NF-κB deacetylation and subsequently reduced the inflammatory response and decreased the TNF-α, IL-6, and IL-10 serum levels; these effects were abolished by SIRT1 inhibition with the selective blocker, Ex527. Correspondingly, melatonin treatment triggered SOD2 deacetylation and increased SOD2 activity and subsequently reduced oxidative stress; this amelioration of oxidative stress by melatonin was blocked by the SIRT3-selective inhibitor, 3-TYP, and was independent of SIRT1. We confirmed this mechanistic effect in a CLP-induced sepsis model of intestinal SIRT3 conditional-knockout mice, and found that melatonin preserved mitochondrial function and induced autophagy of small-intestine epithelial cells; these effects were dependent on SIRT3 activation. This study has shown, to the best of our knowledge, for the first time that melatonin alleviates sepsis-induced small-intestine injury, at least partially, by upregulating SIRT3-mediated oxidative-stress inhibition, mitochondrial-function protection, and autophagy induction.